Large area and robust NiS/Ag electrodes for hydrogen evolution reaction. (2023) - Trivedi, Nandini A.; Patel, Meswa; Pataniya, Pratik M.; Sumesh, C.K.
Abstract: Since a few years, electrocatalytic hydrogen evolution has attracted huge research interests in the production of hydrogen gas. Although noble metals like Pt, Pd, Ru, etc. have shown great potential for water electrolysis, high scarcity ruined the large-scale and efficient production of hydrogen gas. In the present research, NiS based electrocatalyst was synthesized by facile hydrothermal reaction without the use of any toxic and volatile chemical reagents. NiS on Ag-foil shows excellent potential for hydrogen evolution with a low onset potential of about −210 mV and overpotential of about −245 mV at 10 mA/cm 2 cathodic current. Low over potential attributes to the low charge transfer resistance. Encouragingly, NiS/Ag electrode shows highly stable electrocatalytic activity up to 17 h at 10 mA/cm 2 current. Finally, the present investigation on electrolysis of NiS/Ag electrodes demonstrates huge development in the production of non-noble electrocatalysts for efficient hydrogen evolution.